The Study on the Reasons and Cultural Inheritance of Huang Daozhou’s Calligraphy in the "Xiaojing" - liu, sen; Chen , Xuya (Pacific International Journal, 2024)
Huang Daozhou (1585-1646), also known as Shizhai, was a famous scholar and calligrapher of the late Ming and early Qing dynasties. In the final stages of his life, he was imprisoned for his candid advice to the emperor, during which he wrote 120 volumes of the "Xiaojing" (The Classic of Filial Piety). This paper aims to explore Huang Daozhou's motives for writing the "Xiaojing" in prison and its cultural significance. By analyzing Huang Daozhou's life, educational background, reasons for imprisonment, and calligraphy style, the paper reveals the importance of the "Xiaojing" in Huang Daozhou's mind and how he expressed his loyalty and filial piety to the nation and family through his calligraphy. The study shows that Huang Daozhou's calligraphy is not only an artistic creation but also a reflection of his moral and political stance.